Externalities, growth, and regional stagnation - Gunther Maier (European Regional Science Association (ERSA), 1998)
This paper discusses the impact of externalities on economic growth and the long term distribution of economic activities in a system of two regions. We use a standard neoclassical growth model of the Solow-type and augment it with a random process of innovation allocation. The long term behavior of this model is analyzed. As it turns out the dynamic behavior of our model differs fundamentally from that of the standard neoclassical growth model. In the long run always one of hte regions attracts all the future innovation and growth while the other region stagnates. We show that this outcome results from an externality in the process of innovation allocation and discuss its significance and sensitivity to changes in the model structure.
Keywords: 330